ANALISIS PENGARUH EPS TERHADAP HARGA SAHAM (STUDI KASUS PADA PT. AKBAR INDO MAKMUR STIMEC, TBK) - Nur Mima Sari; Nurul Huda (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
This research was taken at PT. Akbar Indo Makmur Stimec Tbk, This research aims to knowing the presence or absence influence EPS on stock prices PT.Akbar Indo makmur stimec tbk.The sample used in this study is 5 years from the year 2014-2018.The sampling technique used is Purposive Sampling. The data analysis technique used is (1) simple linear regression (2) coefficient of determination (3) correlation test (4) hypothesis test T test.The results showed that EPS influence but not significantly to stock price PT. Akbar Indo Makmur Stimec Tbk, with observational years from 2014 to 2018.